Development of Sorghum Flour-Based Edible Straws with Bovine Gelatin and Variations in Carboxymethyl Cellulose Concentration - Deli Silvia; Arifin Agung Setia Budi; Nabila Salma Marshanti; Dextra Syakiella Arumdapta (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2025)
Single-use plastic straw pollution is driving the need for environmentally friendly alternatives. This study aims to develop and characterize edible straws based on sorghum flour with the addition of bovine gelatin and analyze the effect of variations in Carboxymethyl Cellulose (CMC) concentration. A completely randomized design (CRD) was used in a non-factorial format with four levels of CMC concentration (0%, 1%, 3%, and 5%), each with three replications. The straws are made through mixing, semi-wet molding, and two-stage oven drying at 60 °C. The product’s characteristics were tested, including water resistance, absorption, moisture content, organoleptic properties, and biodegradability. Data were analyzed using Analysis of Variance (ANOVA) and Duncan’s Multiple Range Test (DMRT) to determine significant differences between treatments. The analysis showed that adding 3% CMC (C3) produced the optimal formulation, exhibiting the highest water resistance of 63.21 minutes in cold water, the lowest water absorption of 26.2%, and a final moisture content of 8.7%. This formulation also received the highest scores in organoleptic tests for color, aroma, taste, and texture. In contrast, 5% CMC caused the dough to become stiff. Straws show the best resistance to cold water temperatures, followed by normal temperatures. The key finding of this study is that all straw formulations can be fully decomposed (100%) in soil media within 15 days. It was concluded that this sorghum flour-based edible straw has excellent potential to replace conventional plastic straws as a functional and environmentally friendly alternative.